Psychological rebellion and its relationship to violent behavior among students of the Institute of Sciences and Techniques of Physical Activities - Kenioua, Mouloud; Zaoui Sid elcheikh., Mostefa; Grine, Nawal (Journal of Human Sciences, 2022)
The study aimed to identify psychological rebellion and its relationship to violent behavior among students of the Institute of Sciences and Techniques of Physical Activities. The study was conducted on a sample of (80) students at the Institute of Sciences and Techniques of Physical and Sports Activities - Ouargala -. two scale were applied:  The first was Psychological Rebellion Scale, that was prepared by: Al-Jubouri and Heso, the second was Violent Behavior Scale, that was prepared by Farhan.  The results indicated that the level of psychological rebellion and the level of violent behavior were high among students of the Institute of Sciences and Technologies of Physical and Sports Activities  , and There is a positive correlation relationship with statistical significance between psychological rebellion and violent behavior, There are no statistically significant differences in the behavior of violence according to the academic level.